Construction and application of prone position ventilation management scheme for severe COVID-19 patients - Chen, Xiuwen; Peng, Cao; Xiao, Yao; Liu, Shiqing (Frontiers in Physiology, 2023)
Background： Prone position ventilation (PPV) can significantly improve oxygenation index and blood oxygen saturation in most (70–80%) patients with acute respiratory distress syndrome. However, although PPV is not an invasive procedure, there are many potential PPV-related complications, such as nerve compression, crush injury, venous stasis (e.g. facial oedema), pressure sores, retinal damage, vomiting, and arrhythmia, with an incidence of up to 56.9%. Nursing managers have focused on reducing the occurrence of PPV-related complications and improving safety. Objective： To construct a prone ventilation management scheme for patients with severe coronavirus disease 2019 (COVID–19) and analyse its application effect. Methods： Based on a previous evidence-based study combined with the COVID-19 Diagnosis and Treatment Protocol (Trial Edition 9), a prone ventilation management protocol for severe COVID-19 was formulated and applied to COVID-19 patients in the intensive care unit of a designated hospital. A prospective self-control study was used to compare changes in the oxygenation index and other outcome indicators before and after the intervention. Results： The oxygenation index of patients after intervention (321.22±19.77 mmHg) was significantly higher (P < 0.05) than before intervention (151.59±35.49 mmHg). The difference in oxygenation index in different prone position ventilation durations was statistically significant (P<0.05). Nursing quality evaluation indicators showed that the implementation rate of gastric residual volume assessment was 100% and the incidence of occupational exposure and cross-infection was 0%; the incidences of pressure ulcers, drug extravasation, and facial oedema were 13.64% (3/22), 4.54% (1/22), and 4.54% (1/22), respectively. The incidence of unplanned extubation, aspiration, and falls/falls was 0%. Conclusion： The application of a prone ventilation management program for patients with severe COVID-19 can standardise and promote the implementation of prone ventilation, improve the quality of care, and improve patient prognosis.